94.6k views
0 votes
X – 10y = 18
-6x – 10y = 32

User Morendo
by
5.2k points

1 Answer

2 votes

Answer:

Explanation:


x - 10y = 18


-6x - 10y = 32

Since both equations have
-10y, we can subtract the second equation from the first to try and solve for
x:


(x - 10y) - (-6x - 10y) = 18 - 32


x - 10y + 6x + 10y = -14


7x = -14


x = -2

With this, we can plug the value back into the first equation to solve for
y:


(-2) - 10y = 18


-2 - 10y = 18


-10y = 20


y = -2

Therefore, the solution is
x = -2, y = -2

User Rafael
by
5.4k points